2001
DOI: 10.1021/ic000958v
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Design (CAD) of Mn(II) Complexes:  Superoxide Dismutase Mimetics with Catalytic Activity Exceeding the Native Enzyme

Abstract: New Mn(II) macrocyclic pentaamine complexes derived from the biscyclohexyl-pyridine complex, M40403 ([manganese(II)dichloro[(4R,9R,14R,19R)-3,10,13,20,26-pentaazatetracyclo[20.3.1.0.(4,9)0(14,19)]hexacosa-1(26),-22(23),24-triene]]), are described here. The complex M40403 was previously shown to be a superoxide dismutase (SOD) catalyst with rates for the catalytic dismutation of superoxide to oxygen and hydrogen peroxide at pH = 7.4 of 1.2 x 10(+7) M(-1) s(-1).(1) The use of the computer-aided design paradigm r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(148 citation statements)
references
References 21 publications
(31 reference statements)
5
142
1
Order By: Relevance
“…Our data show that such high thermodynamic and kinetic facilitation, which leads to an exceptionally high k cat for the O 2 •− disproportionation, can be achieved not only with an N 5 -type coordination motif, as rationalized previously for aza crown ether (cyclic polyamines) complexes [47][48][49], but also with a N 4 -type motif as in the Mn porphyrin case. Interestingly, both aza crown ethers and β-octabrominated porphyrins [12] share a common alternating "up-down-up-down" steric arrangement of the nitrogens around the Mn center, which is presumably critical for the dismutation process [47][48][49]. Thus, future work on molecules that possess appropriate geometries for efficacious catalysis is highly justifiable.…”
Section: Protection Of Aerobic Growth Of Sod-deficient E Colisupporting
confidence: 82%
“…Our data show that such high thermodynamic and kinetic facilitation, which leads to an exceptionally high k cat for the O 2 •− disproportionation, can be achieved not only with an N 5 -type coordination motif, as rationalized previously for aza crown ether (cyclic polyamines) complexes [47][48][49], but also with a N 4 -type motif as in the Mn porphyrin case. Interestingly, both aza crown ethers and β-octabrominated porphyrins [12] share a common alternating "up-down-up-down" steric arrangement of the nitrogens around the Mn center, which is presumably critical for the dismutation process [47][48][49]. Thus, future work on molecules that possess appropriate geometries for efficacious catalysis is highly justifiable.…”
Section: Protection Of Aerobic Growth Of Sod-deficient E Colisupporting
confidence: 82%
“…Riley et al (21,204,269,277) developed Mn complexes with cyclic polyamines=tetraaza crown ethers as catalysts for O 2 ·À dismutation (Fig. 9).…”
Section: A Sod-like Activitymentioning
confidence: 99%
“…9). Structural modifications led to compounds of increased activity; complexes with k cat as high as 10 9 Ms have been reported (21). The detailed kinetic study published by Maroz et al (204) found that the reaction of a transient adduct (formed with the first O 2 ·À molecule) with the second molecule of O 2 ·À is particularly dependent on the structure of the polyamine.…”
Section: A Sod-like Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Euk-8 and Euk-134 were generous gifts from Dr. Susan Doctrow, Eukarion Inc., Bedford, MA. The Metaphore compounds were generously supplied by Dr. Dennis Riley, Metaphore Pharmaceuticals, Fort Lee, NJ, or synthesized as described [39]. MnTBAP (manganese tetrakis (4-benzoic acid) porphyrin) was purchased from Oxis International Inc., Portland, OR or Calbiochem, San Diego, CA.…”
Section: Manganese Mimic Compoundsmentioning
confidence: 99%